1998
DOI: 10.1021/bi972914c
|View full text |Cite
|
Sign up to set email alerts
|

Ro 09-2210 Exhibits Potent Anti-proliferative Effects on Activated T Cells by Selectively Blocking MKK Activity

Abstract: By using high throughput screening of microbial broths, we have identified a compound, designated Ro 09-2210, which is able to block anti-CD3 induced peripheral blood T cell activation with an IC50 = 40 nM. Ro 09-2210 was also able to block antigen-induced IL-2 secretion with an IC50 = 30 nM, but was considerably less potent at blocking Ca2+ flux stimulated by anti-CD3 treatment. To determine the mechanism of action of Ro 09-2210, we set up a transient expression system in Jurkat T cells using a variety of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Two compounds, Ro092210 and L783277, with very similar structures to 5Z-7-oxozeaenol were previously demonstrated to inhibit MEK kinase activity (17,18). We examined the effect of 5Z-7-oxozeaenol on purified rat MEK1 kinase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two compounds, Ro092210 and L783277, with very similar structures to 5Z-7-oxozeaenol were previously demonstrated to inhibit MEK kinase activity (17,18). We examined the effect of 5Z-7-oxozeaenol on purified rat MEK1 kinase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MEK inhibitor Ro 09-2210 has been less well-characterized in terms of its specificity profile or antiinflammatory potential, but it has also been shown to inhibit LPS-induced TNF production in monocytes (49) and the proliferation and activation of T cells (50). Array BioPharma (Boulder, CO) is also developing potent and selective MEK inhibitors (16) and has reported significant efficacy data in animal models of inflammation and arthritis (51), further supporting the pivotal role of this kinase in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Later on, other studies showed that overexpression of interfering mutants of MEK1 (Cowley et al, 1994;Seger et al, 1994), incubation with ERK2 antisense oligonucleotide (Sale et al, 1995) or expression of active MAP kinase phosphatase 1 (MKP-1/DUSP1) (Sun et al, 1994;Brondello et al, 1995) inhibits the induction of DNA synthesis by serum and activated Ras. Similarly, treatment with synthetic MEK1/2 inhibitors, which prevents activation of ERK1/ERK2, was reported to inhibit the proliferation of various cell types, including fibroblasts, T lymphocytes, smooth muscle cells, hepatocytes and epithelial cell lines (Dudley et al, 1995;Seufferlein et al, 1996;Karpova et al, 1997;DeSilva et al, 1998;Williams et al, 1998;SeboltLeopold et al, 1999;Talarmin et al, 1999). Conversely, expression of constitutively active forms of MEK1 (Brunet et al, 1994;Cowley et al, 1994;Seger et al, 1994) relaxes growth factor dependency and enhances the rate of cell proliferation.…”
Section: Sustained Activation Of the Erk1/2 Map Kinase Pathway Is Necmentioning
confidence: 99%